- Keabsahan Hukum Penerbitan Sertipikat Tanah Elektronik Sebagai Alat Bukti Kepemilikan Hak Atas Tanah Di Persidangan: - - Michelle Priscilla; Nova, Dini Laelatul; Fajriah, Septi Naelina (UIR Law Review, 2024)
This study examines the legal validity of electronic land certificates in Indonesia, particularly in the context of land ownership and dispute resolution. The research aims to investigate the legal framework governing electronic land certificates, their admissibility as evidence in court, and their potential impact on land ownership disputes. The study reveals that electronic land certificates, introduced by the Indonesian government in 2021 have the same legal force as analog paper-based certificates. The certificates, issued through an electronic system, provide proof of land ownership and are recognized by the government as a valid means of establishing ownership. However, concerns regarding the security and integrity of the electronic system, as well as the potential for fraud and manipulation, need to be addressed to ensure the reliability and credibility of electronic land certificates. The study concludes that electronic land certificates have the potential to enhance the efficiency and transparency of land ownership transactions, but their legal validity and admissibility in court require further clarification and standardization. Keywords electronic land certificates; legal validity; land ownership; dispute resolution.